PENGARUH PAD, DAU DAN DAK TERHADAP BELANJA LANSUNG - Rahmat, Aris; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is aimed to prove empirically the influence of Local Own Sources Revenue (PAD), General Allocation Fund (DAU), and Special Allocation Fund (DAK) to the Direct Expenditure Allocation at Districts / Cities in Surabaya, Bangkalan, Gresik, Pamekasan, Sampang and Sumenep which are located in East Java. The population and samples are 6 governments of districts and cities in East Java. The period of sample observation is from 2010 until 2014.The research method has been conducted by using quantitative research and the secondary data collection technique. The data has been collected by using documentation method and it has been carried out by collecting, recording and calculating the data which are related to the research which have been done by using census method and then collecting six population of Districts/Cities i.e. Surabaya, Bangkalan, Gresik, Pamekasan, Sampang dan Sumenep. The research object has been done by using the document of the realization report of Regional Government Budget of districts / cities of Surabaya, Bangkalan, Gresik, Pamekasan, Sampang dan Sumenep and it has been obtained from the official sites of Directorate General of Local Government Financial Balance in the internet from 2010 to 2014. The data analysis technique has been carried out by using descriptive statistic, classic assumption test, regressions equation, and hypothesis test which consist of value of coefficient determination, statistic F value and t statistic value. The result of this research shows that Local Own-Source (PAD), General Allocation Fund (DAU), has significant and positive influence to the Direct Expenditure Allocation. Meanwhile, Special Allocation Fund (DAK) does not have any significant and positive influence to the Direct Expenditure Allocation.Keywords: Local Own-Sources (PAD), General Allocation Fund (DAU), and Special Allocation Fund (DAK), Direct Expenditure Allocation.